2017
DOI: 10.1016/j.apmr.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Assisted Movement Therapy in Chronic Stroke Patients With Severe Upper Limb Paresis: A Pilot, Single-Blind, Randomized Crossover Study

Abstract: EAMT produces a clinically important impairment reduction in stroke patients with chronic, severe upper limb paresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Since the patients in the present study were relatively severely paralyzed, articles in which the participants' FMA score was less than 15 points were selected to discuss the effect size of interventions. Using these inclusion criteria, six articles were selected (Stinear et al, 2008;Ramos-Murguialday et al, 2013, 2019Colomer et al, 2016;Grimm et al, 2016;Carda et al, 2017). Among those, the effect size was more than medium (Cohen's d > 0.5) in only two articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the patients in the present study were relatively severely paralyzed, articles in which the participants' FMA score was less than 15 points were selected to discuss the effect size of interventions. Using these inclusion criteria, six articles were selected (Stinear et al, 2008;Ramos-Murguialday et al, 2013, 2019Colomer et al, 2016;Grimm et al, 2016;Carda et al, 2017). Among those, the effect size was more than medium (Cohen's d > 0.5) in only two articles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical trials for patients with stroke in the chronic phase were reported. The effect size of the mirror therapy (Colomer et al, 2016) or functional electrical stimulation (Carda et al, 2017) intervention may be insufficient. Additionally, clinical trials using the brain-machine interface have demonstrated a higher effect size (Ramos-Murguialday et al, 2013, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst all, these selected trials were different in study quality: besides 12 17,18,26,[28][29][30][31][32][33][34][35][36] blind trials were at low risk of bias, one study 27 was assessed as high risk of bias out of not blind. 2 35, 36 trials adopted concealed allocation, which were regarded as low risk of bias.…”
Section: Data Qualitymentioning
confidence: 99%
“…One study 34 was at high risk of bias due to incomplete outcome data. Moreover, 6 studies 17,18,28,31,33,35 were at low risk of bias due to random sequence generation by computer or pseudorandom number sequence. One study 36 was at high risk of bias for free of other sources of bias.…”
Section: Data Qualitymentioning
confidence: 99%
“…Other limitations of the latest wearable, wireless FES systems include the low resolution of induced muscle contraction, the absence of veri iable algorithms to expand the utility of FES to train non-walking daily functions including training to stand up and sit down independently. The limited availability of clinically valued coupling of FES with other rehabilitation technologies such as EEG controlled FES [55,56], or wearable robots and virtual reality systems [57], is also recognized in the literature [36]. Attempts to improve the resolution of FES induced muscle contraction by using multiplexers and arrays of small electrodes [39,58] or manipulation of pulse parameters [1] have yielded some interesting discoveries and electronic innovations.…”
Section: Fes As a Clinical Training Toolmentioning
confidence: 99%